A shift from “habitat pour le plus grand nombre” to “habitat évolutif” in post‐war francophonie: A study on the history of international and regional exchange activity of ATBAT(Atelier des Bâtisseurs), part 2 - Kosuke Matsubara (Japan Architectural Review)
Abstract As a continuation of my previous paper “Part 1” which is titled “Formation and change of an international exchange organization,” the scope of this paper encompasses the period of ATBAT (Atelier des Bâtisseurs)'s work in Morocco, via the manifestation at CIAM 9, up to the point of their separation. In this paper I also conduct certain planning studies for the purpose of examining how the “habitat pour le plus grand nombre (hereafter ‘housing for the greatest number’)” movement led to the “Évolutif (evolutionary)” concept; finally to the planning method known as “Habitat Évolutif (Evolutionary Housing)” is examined. The way in which this last method was concretized through the exchange of ideas proposed by members particularly those proposed by Banshoya are elaborately examined. The most important roles played by ATBAT was (1) to expand the idea of new housing style suggested by Le Corbusier based on their technical research, and (2) to examine it with general people including slum residents in the various cities in Francophonie, and (3) to find the planning methods of Habitat Evolutif. The beginning of the idea of Habitat Evolutif can be already seen in the theory of Le Corbusier, but it was ATBAT’s original contribution to give a theoretical framework in it based on their international and regional exchange activities.